The Use of Language in Anti-Bullying Campaigns on Social Media - Nur Indah Sari; Eka Septiani (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This research aims to analyze the use of language in anti-bullying campaigns on social media, identify the types of language most effectively used in anti-bullying campaigns on social media, and understand the impact of language use in anti-bullying campaigns on public opinion. The method used is a qualitative approach with content analysis of 100 social media posts (Instagram, Facebook, and Twitter). The research results show that communication strategies using persuasive, emotive, and informative language effectively influence public opinion. Simple language, images, and videos are the most effective types of language. Language Communication Strategy: Persuasion (40%), emotive (30%), informative (30%). Type of Language: Simple language (60%), images (20%), videos (20%). Language Effectiveness: 80% of posts influence public opinion. Factors influencing the effectiveness of language: Source credibility (50%), content relevance (30%), audience interaction (20%). The conclusion of this research is that it can contribute to the development of effective communication through language in anti-bullying campaigns on social media and identify the language variables that influence the effectiveness of anti-bullying campaigns.